Pengaruh Kemampuan Akademik, Persepsi Profesi Akuntan Publik, Pertimbangan Pasar Kerja Dan Penerapan Ajaran Tri Nga Terhadap Minat Mahasiswa Akuntansi Memilih Karier Sebagai Akuntan Publik - Zerah Insani Sallata (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine whether academic ability, perceptions of the public accounting profession, labor market considerations and application of Tri Nga affect the interest of accounting students in choosing careers as public accountants. This research uses a quantitative descriptive method with primary data using a questionnaire. This study took a sample of 140 accounting students from 3 universities in Yogyakarta, i.e. Sarjanawiyata Tamansiswa University, Sanata Dharma University and Indonesian Islamic University. The sampling technique used purposive sampling. Data collection was carried out by distributing questionnaires via google form. The number of questionnaires processed was 140 questionnaires. Data processing was performed using multiple linear regression analysis. The results of this study indicate that perceptions of the public accounting profession and labor market considerations have a positive effect on the interest of accounting students in choosing careers as public accountants, while academic ability and application of Tri Nga have no effect on the interest of accounting students in choosing careers as public accountants. Keyword : Academic Ability; Public Accountant Professional Perceptions; Labor Market Considerations; Application of Tri Nga; Student Interest